Verkehrssicherheit von Radfahrern - Analyse sicherheitsrelevanter Motive, Einstellungen und Verhaltensweisen. - Below, Ariane von (My University, 2016)
Radfahren schont die Umwelt und ist gesund, doch Radfahrer leben auch gefährlich. Der Rückgang der Verunglücktenzahlen bleibt hinter der allgemeinen Unfallentwicklung zurück. Die Bundesanstalt für Straßenwesen (BASt) führte eine repräsentative Befragung zum Fahrradfahren durch und analysierte eine große Anzahl von Fahrradunfällen. Die Ergebnisse ermöglichen die Entwicklung neuer Maßnahmen für die Verkehrssicherheit.

Cycling is environmentally friendly and good for people's health, but also very dangerous. The decline in the number of cyclists injured in road traffic accidents is currently lagging behind the general trend in accident statistics. The Federal Highway Research Institute (BASt) conducted a representative survey among cyclists and analysed a wide range of accidents involving bicycles. The results of this study enable the development of new traffic safety measures. There is, for instance, the necessity to raise public awareness for the risks of cycling under the influence of alcohol or for the distraction from mobile electronic devices. Theory-based courses or practical cycle training might be envisaged to refresh knowledge of the Highway Code. Intensified monitoring and sanctioning of cyclists' misconduct and targeted checks with the involvement of the media might be sensible. The construction of cycling infrastructure in accordance with regulations also contributes to a reduction of misconduct among cyclists. Presenting an increasingly positive image of cycle helmet use can serve to raise the share of cyclists voluntarily choosing to wear them. In order to reduce the severity of injuries suffered in traffic accidents, the ongoing development of technical vehicle equipment should be expedited. This could include bicycle airbags as well as car-to-bike communication equipment. Presenting an increasingly positive image of cycle helmet use can serve to raise the share of cyclists voluntarily choosing to wear them. In order to reduce the severity of injuries suffered in traffic accidents, the ongoing development of technical vehicle equipment should be expedited. This could include bicycle airbags as well as car-to-bike communication equipment.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Erhebung; Auswertung; Fahrradunfall; Radfahrer